Directions of Development of Transport Networks and Traffic Engineering 15th Scientific and Technical Conference "Transport Systems. Theory and Practice 2018", Katowice, Poland, September 17-19, 2018, Selected Papers - Macioszek, Elżbieta; Sierpiński, Grzegorz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a collection of valuable guidelines for making decisions concerning the future development of transport networks and traffic engineering. The decision-making support systems described here will certainly attract the interest of those who face the challenge of finding solutions to problems concerning modern transport systems on a daily basis. Consequently, the book is chiefly intended for local authorities involved in planning and preparing development strategies for specific transport-related areas (in both urban and regional contexts), as well as for representatives of business and industry who are directly engaged in the implementation of traffic engineering solutions. The guidelines provided in the respective chapters help to address the given problem soundly, and to simplify the selection of an appropriate strategy. The topics covered include increasing the competitiveness of public transport, the status quo of electric vehicle infrastructures worldwide, methods for calming urban traffic as an element of sustainable transport development, speed traffic zones and electric buses, car-sharing systems in Poland, a method for deconstructing the regional travel demand model, monitoring urban traffic using floating car data, problems of deliveries in urban agglomeration distribution systems, estimating the number of threatened people in case of fire in road tunnels, and road pavement evaluation using advanced tools. Since the book also considers new approaches to theoretical models (including traffic flow surveys and measurements, transport behaviors, human factors in traffic engineering, and road condition modeling), it will also appeal to researchers and scientists studying these problems. The book gathers selected papers presented at the 15th Scientific and Technical Conference "Transport Systems. Theory and Practice", organized by the Department of Transport Systems and Traffic Engineering, Silesian University of Technology in Katowice, Poland on September 17-19, 2018.
Keywords: Computational intelligence; Transportation engineering; Traffic engineering; Artificial intelligence; Computational Intelligence; Transportation Technology and Traffic Engineering; Artificial Intelligence